Video streaming based on frames skipping and interpolation techniques - Fadlallah, Fadlallah Ali; Khalifa, Othman Omran; Hassan Abdalla Hashim, Aisha (The Institute of Electrical and Electronics Engineers, Inc., 2016)
This paper proposed a video frame skipping and interpolation technique (VFS-I) for streaming video. This technique is divided into main sections: transmitter and receiver. The transmitter is employed FSM (Frame Skipping Mechanism) to drop/skip similar frames from video sequence to reduce the amount of frames that need to be transferred over the network. This method specified frames to-be-kipped according to motion estimation between every neighboring frame. After that, re-encode the remaining video frames, and sent it to the receiver. The receiver employed RFI (Reconstructing video-Frames Interpolation) to rebuild the frames that were dropped in the transmitter side. The motion compensated interpolation of the key-frame (remaining frame) is used to reconstruct video frames back. A unified design of frame-skipping and interpolation mechanism are made for incrementing and improving compression process efficiency that have not considered in the previous works. One of the main advantages of the VFS-I is characterized by flexibility and scalability of video streaming to the requirements of the network bandwidth and end user